Reconstructing the Cryogenian–Ediacaran evolution of the Porongos fold and thrust belt, Southern Brasiliano Orogen, based on Zircon U–Pb–Hf–O isotopes. Issue 12 (10th September 2017) - Pertille, J.; Hartmann, L. A.; Santos, J. O. S.; McNaughton, N. J.; Armstrong, R.
ABSTRACT: The Neoproterozoic geotectonic triad of the Brasiliano Orogen is reconstructed in southern Brazil from studies focused on the Porongos fold and thrust belt. We integrate field geology with isotopic studies of zircon U–Pb SHRIMP and Lu–Hf–O laser determinations in seven metasedimentary and three metavolcanic rock samples. The results indicate that the Porongos palaeo-basin was derived from mixed sources (3200–550 Ma), with major contributions from Rhyacian (2170 Ma) and Ediacaran (608 Ma) sources. Minor contributions from Archaean to Tonian sources are also registered. The maximum depositional age of the Porongos palaeo-basin is established by the age range of 650–550 Ma with T DM model ages between 2.5 and 1.3 Ga. The reworked signature ( ε Hf values = −34 to −4) and the characteristic crustal magma reservoirs ( δ 18 O ≥5.3 ‰) indicate that these sediments are equivalent to Neoproterozoic granites of the Dom Feliciano Belt. The episodic depositional history started in the Cryogenian (650 Ma) and lasted until the Ediacaran (most likely 570 Ma). A magmatic event of Tonian age is recorded in rhyodacite samples interleaved with the metasedimentary rocks and dated at 773, 801, and 809 Ma. The crustal evolution of the Sul-Riograndense Shield included mountain building, folding and thrusting and flexural subsidence in the foreland. An orogenic triad is revealed as the Pelotas Batholith, the Porongos fold and thrust belt and the Camaquã Basin, all part of the Dom Feliciano Belt.